How to effectively use online medical records: A moderated mediation analysis of patient-centered communication and self-efficacy in mitigating anxiety among patients with chronic diseases - Zhang, Luxi; Liu, Tianyi; Xu, Lunan; Zhao, Xinshu (Journal of health psychology, 2025)
Online Medical Records (OMR) aim to improve chronic disease management, but literature on their association with anxiety is inconclusive, especially in the context of patients having full access to their online medical record documentation. This study developed and tested a moderated mediation model linking OMR use to anxiety using data from 2663 chronic disease patients in the 2022 Health Information National Trends Survey (HINTS6). Our findings suggest that while the perception of conflicting health information resulting from OMR usage is positively associated with anxiety, enhancements in patient-centered communication (PCC) through OMR can help mitigate this effect. The moderating effect of health information self-efficacy indicates that individual differences may affect the extent of benefits from OMR usage for chronic disease patients. Findings highlight the role of PCC in managing emotional responses to digital tools. Promoting PCC and tailored education may support effective and equitable OMR use.